Constant Market Share Analysis of the ASEAN Timber Trade - Othman, Shahwahid; Abdul Rashid, Zakariah (Universiti Putra Malaysia Press, 1993)
This paper investigates the growth in exports of ASEAN wood products during sub-periods of recessive and active world trade patterns that were experienced between 1979 to 1987. The Constant Market Share Analysis was used to measure ASEAN export growth performance relative to average growth in world export of wood products. It was found that the ASEAN wood products export trade was susceptible to world economic conditions. The structure of ASEAN'S wood products export in terms of the lack of commodity and market diversifications has further contributed to the lack in market share improvements. A review of some ASEAN policies at diversifying its wood product commodities are provided in the paper.